Fra agrilogistik til økokonvivialitet: Fremskridtsfortællingens sammenbrud og utopiske modsvar i dansk og tysk rural samtidslitteratur - Wennerscheid, Sophie (Passage - Tidsskrift for litteratur og kritik, 2026)
From Agri-logistics to Eco-Conviviality: The Collapse of the Narrative of Progress and Utopian Responses in Contemporary Danish and German Rural Literature This article examines how literature portrays agriculture as a practice that shapes landscapes, values, imaginaries, and behaviour. Reading two novels, a manifesto, and a poetry collection, it traces these dynamics across distinct registers: the novels chart the gradual wearing-down of landscapes and rural belonging under modern agrarian logics, while the other works reimagine cultivation as a future-facing practice of ecological care, rendering palpable the aesthetic textures of eco-convivial regeneration.